DYNAMIC SPECIATION OF TRACE METALS IN AQUATIC ENVIRONMENT USING ANODIC STRIPPING CHRONOPOTENTIOMETRY - Costa Monteiro, Adnivia Santos [UNESP]; Goveia, Danielle [UNESP]; Rotureau, Elise; Rosa, Andre Henrique [UNESP]; Masini, Jorge Cesar; Pinheiro, Jose Paulo (Soc Brasileira Quimica, 2018)
The contamination of natural environments by trace metals has several adverse effects on human health, which is mainly due to the high toxicity, persistence and reactivity of these species in the environment. To understand the bioavailability of trace metals, it is necessary to know the speciation in equilibrium and the dynamic behavior of the system. In this context, the present work aims to present a bibliographic review about the potentialities of the Stripping Chronopotentiometry (SCP) and Stripping Chronopotentiometry at Scanned Deposition Potential (SSCP) in the study of dynamic trace metal speciation. These techniques have low detection limits and do not suffer interference due to the adsorption of organic matter on the surface of the working electrode. Coupling these techniques with the Absence of Gradients and Nernstian Equilibrium Stripping (AGNES) enables simultaneous determination of free ions, complexation equilibrium constants and diffusion coefficients of the complexes, thus providing information on the dynamic and heterogeneity of the metal complexes in the presence of macromolecules or particles. In this paper we will present the theory of dynamic speciation of trace metals, a detailed description of how to use the techniques to obtain this information, and examples of application in model systems and natural samples.
Keywords: metal complexes; metal ions; lability; redissolution techniques; deposition time